A review on the exploration of nanomaterials application in pavement engineering - Abdullah, Mohd. Ezree (Penerbit UTM Press, 2015)
In order to improve the performance of asphalt mixture, the virgin asphalt binder needs to be modified with suitable modifiers. There are various types of modifiers available in market and it is clearly stated and established in most of pavement standard specification. Nowadays, pavement technologist and researchers had put their interests on nanotechnology and they had found that polymeric nanocomposites have shown its effectiveness through the modification of virgin asphalt binder with certain portion of nanomaterials. In addition, many studies have demonstrated that nanomaterials have significant effects in improving the engineering properties of asphalt binder and mixture. Therefore, a thorough literature review on the current research of nanomaterials in pavement engineering for the past decades can enhance understanding and guaranteed something beneficial findings in the future. This paper described the theory of nanotechnology and its historical development including the method used among researchers in evaluation the structural and morphological characteristics of modified binder with nanoparticles. Also, the effect of different types of nanoparticles, suitable dosages, modifying procedures, problems and benefits on asphalt binder and mixture were explained. It is expected that in future the implementations of nanotechnology would have major impacts for better pavement performance.